Pengaruh Kesadaran Wajib Pajak, Sanksi Pajak dan Pengetahuan Pajak Terhadap Kepatuhan Wajib Pajak dalam Pembayaran PBB di Kecamatan Cigombong - Anur, Aulia Sari; Kusuma, Indra Cahya; Melani, Maria Magdalena (LPPM Akademi Akuntansi Indonesia, 2024)
This study intends to analyze the impact of awareness, sanctions and knowledge on PBB payment compliance. Taxpayer compliance is very important to support regional development financing and community welfare. This study uses a quantitative type of study through survey techniques among the people of the Cigombong area who have UN obligations. The collected information was analyzed using multiple regression to test the influence of each variable on compliance with paying levies. The study results illustrate that awareness has a positive impact on PBB compliance, sanctions have a negative impact on PBB compliance and knowledge has no impact on PBB compliance. Meanwhile, testing simultaneously shows that awareness, sanctions and knowledge have a positive impact on PBB compliance